2020
DOI: 10.1007/s12975-020-00869-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Correlates of Hemorrhage and Edema Volumes Following Human Intracerebral Hemorrhage Implicate Inflammation, Autophagy, mRNA Splicing, and T Cell Receptor Signaling

Abstract: Intracerebral hemorrhage (ICH) and perihematomal edema (PHE) volumes are major determinants of ICH outcomes as is the immune system which plays a significant role in damage and repair. Thus, we performed whole-transcriptome analyses of 18 ICH patients to delineate peripheral blood genes and networks associated with ICH volume, absolute perihematomal edema (aPHE) volume, and relative PHE (aPHE/ICH; rPHE). We found 440, 266, and 391 genes correlated with ICH and aPHE volumes and rPHE, respectively (p < 0.005,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 116 publications
0
29
1
Order By: Relevance
“…Siponimod, for example, has shown a tendency to reduce intracerebral edema. Experimental intracerebral edema is a prominent cause for the increase in neurobehavioral scores in mice ( Durocher et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Siponimod, for example, has shown a tendency to reduce intracerebral edema. Experimental intracerebral edema is a prominent cause for the increase in neurobehavioral scores in mice ( Durocher et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular hemoglobin rapidly oxidized from a ferrous state to a highly reactive iron state. Proliferation, differentiation, and axon growth of germ cells were then prevented by activating cytotoxic, oxidative, and inflammatory pathways ( 17 , 18 ). Another study showed that their cerebral cortex was composed of promyelin oligodendrocytes and oligodendrocyte precursor cells, for premature babies <32 weeks after birth.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that infiltrating T cells may interact with the cerebrovasculature in the acute phase after ICH to aggravate damage to the BBB, which results in increased brain water volume and worsened outcomes in experimental models. Th17 and CD8+ T cells can cause endothelial dysfunction or death following ICH [26,32,42]; however, genomic sequencing data identifying other antigen-dependent and independent mechanisms suggest the more complex action of T cells, which remain to be determined in the ICH brain [44]. With the adoption of single-cell RNA sequencing, we now have the ability to catalog the transcriptomic profile of T cells at an individual resolution across time and specific compartments, giving insights into the mechanisms underlying their damage to the endothelium.…”
Section: T-cell-mediated Endothelial and Nvu Dysfunctionmentioning
confidence: 99%